ASSESSMENT OF COGNITIVE LOAD USING PUPILLOMETRIC MEASURES IN NEURO-TYPICAL POPULATION: APPLICATION IN FORENSIC SCIENCES - Kakkar, Aishwarya; Kumari, Leena; Kumar, Vijay (Journal of Forensic Medicine and Toxicology, 2024)
The process of measuring the change in the diameter of the pupil is called pupillometry. The pupil dilates and constricts quickly as a response to either change in the brightness of the visual field or a change in cognitive workload. Task induced dilation of pupils under controlled conditions such as light intensity, the posture of the body, emotional status, and arousal is called the task-evoked pupillary response (TEPR). The measurement of pupillary movements may be used to reliably and involuntarily index the extent of central processing allocated to a particular cognitive task. The objective of the present study is to find if Pupillometry can tap change in cognitive load and play a role in determining and assessing language processing, using music as stimuli. 20 adult undergraduate regular University students participated in this study; the population was primarily Hindi speaking. Peak dilation (PD) of both the Right and Left eyes was measured using a Pupillometer. Measurement was taken under the 1) standard clinical condition (baseline) and other conditions with earphones on; 2) instrumental music, 3) regular Bollywood Hindi rap music and 4) foreign music were played (experimental condition). Analysis was done across various conditions, using SPSS. T-test analysis was also done. Peak dilation across typical conditions and with three cognitive load conditions (music) was calculated. A significant difference across the conditions (p
Keywords: Pupillometry; Cognitive Load; Language Processing; Speech Perception; Linguistic Complexity